Digital Assesment Development of Emotioal Regulation Measurement Tools in Children with Down Syndrome - Putri, Sunita Rahayu; Zahra, Fatimatuz; Laili, Fadzila Nur; Tsurayya, Husna; Sholichah, Ima Fitri (Jurnal Psikologi Teori dan Terapan, 2025)
Background: Down Syndrome is a genetic disorder that often affects emotional regulation in individuals. Children with down syndrome usually have difficulty understanding and expressing their emotions appropriately. Objective: The purpose of this study was to test the factor structure of the digital version of the ERQ for down syndrome children, which is called the DTbERQ (Digital Technology-based Emotion Regulation Questionnaire). Method: The subjects used in this study were 39 parents or guardians of a child with down syndrome in the city of Gresik-Surabaya. This study involved 2 translators and 2 expert judges. Then a readability test was carried out on 3 subjects before using the DTbERQ on a large scale. The analysis of this study used statistical procedures for validity and reliability tests. Results: The results of this study show that the DTbERQ measuring instrument has proven to be valid and reliable for measuring the emotional regulation of down syndrome children. Conclusion: The DTbERQ measuring instrument can be used well to measure the emotional regulation of children with down syndrome from the perspective of parents or those closest to them. Keywords: Digital assesment; down syndrome; DTbERQ; emotion regulation. Abstrak Latar Belakang: Down Syndrome adalah kelainan genetik yang seringkali mempengaruhi regulasi emosi pada individu. anak-anak dengan down syndrome sering menghadapi kesulitan dalam memahami dan mengekspresikan emosi mereka secara tepat. Tujuan: Tujuan dari penelitian ini yaitu untuk menguji struktur faktor ERQ versi digital untuk setting anak down syndrome yang disebut dengan DTbERQ (Digital Technology based Emotion Regulation Questionnaire). Metode: Subjek yang digunakan dalam penelitian ini adalah sebanyak 39 orang tua atau wali dari anak down syndrome yang ada di kota Gresik-Surabaya. Penelitian ini melibatkan penerjemah 2 orang dan 2 expert judgement. Kemudian dilakukan uji keterbacaan kepada 3 subjek sebelum menggunakan DTbERQ dalam skala yang besar. Analisis penelitian ini menggunakan prosedur statistik uji validitas dan reliabilitas. Hasil: Hasil penelitian ini adalah bahwa alat ukur DTbERQ terbukti valid dan reliabel untuk mengukur regulasi emosi anak down syndrome. Simpulan: Alat ukur DTbERQ dapat digunakan dengan baik untuk mengukur regulasi emosi anak down syndrome melalui sudut pandang orang tua atau orang terdekat. Kata Kunci: Asesmen digital; down syndrome; DTbERQ; regulasi emosi.